Graphite tailings foam concrete, method for preparing same and use thereof
Patent Information
- Application Number
- CN202411867607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-12-18
AI Technical Summary
[0004]尽管EMAS在工程应用中取得成功,但EMAS系统中的核心拦阻材料泡沫混凝土在铺设和服役的过程中,会因机场气候温度和雨雪的共同作用,导致其因吸水率大而出现裂纹、粉化和力学性能显著下降等问题,造成拦阻效果降低或失效
(1)本发明制备的石墨尾矿泡沫混凝土具有耐水性能,力学性能稳定和具有良好而稳定的能量吸收能力,符合《特性材料拦阻系统》MH/T 5111-2015要求。
Smart Images

Figure CN119430994B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of aircraft runway arresting systems, specifically relating to a graphite tailings foamed concrete, its preparation method, and its application. Background Technology
[0002] Foamed concrete, with its low density, high porosity, excellent buffering and energy absorption effects, and adjustable strength, is widely used as a building insulation and energy-absorbing material. In recent years, to address the problem of personnel and property damage caused by aircraft overrunning the runway, foamed concrete has begun to be used as an arresting material in Engineered Material Arresting Systems (EMAS) to prevent the hazards caused by runway overruns. This EMAS primarily uses foamed concrete (FC) as the core arresting material. When an aircraft overruns the EMAS, the arresting material is crushed to absorb the aircraft's kinetic energy appropriately.
[0003] Currently, researchers both domestically and internationally are dedicated to developing low-density, high-strength foamed concrete. However, foamed concrete used in aircraft pavement arresting systems must meet specific strength ranges, possess good energy absorption characteristics, and have a certain degree of crushing ability. To ensure that foamed concrete maintains good arresting performance throughout the service life of the EMAS (Electrical Arresting System) and enhances the safety, effectiveness, and designability of aircraft arresting, the stress deviation of the plateau segment of the mechanical property curve (i.e., stress-crushability curve) of foamed concrete during its service life must be stable within ±10% of the design range (Fang Jun. Preparation and Performance Study of Ultra-Lightweight Concrete for Aircraft Arresting Systems [D]. China Building Materials Academy, 2020.). When EMAS is subjected to aircraft wheel crushing, the arresting material (foamed concrete) undergoes compression, crushing, and compaction into powder. However, compressive strength is insufficient to characterize the compression process of foamed concrete in EMAS. It is necessary to characterize the energy absorption capacity of the arresting material (foamed concrete) after it is crushed by the aircraft wheel. According to the "Characteristic Materials Arresting Systems" (MH / T 5111-2015), the rate of change of the collapse strength of foamed concrete during service should not exceed 20%.
[0004] Despite the success of EMAS in engineering applications, the core arresting material, foamed concrete, suffers from problems such as cracking, pulverization, and significant degradation of mechanical properties due to high water absorption caused by the combined effects of airport climate temperature and rain / snow during installation and service. This leads to reduced arresting effectiveness or even failure. Sun Yumei et al. (Research on the arresting performance of EMAS core layer under freeze-thaw conditions [D], Tianjin University of Technology, 2017) studied the performance of foamed concrete in EMAS under freeze-thaw conditions and found that freeze-thaw cycles cause the expansion of defects in the EMAS core layer, which gradually evolves into structural damage. This damage reduces the mechanical properties and durability of foamed concrete, thereby increasing the aircraft arresting distance and increasing safety risks. Therefore, how to improve the durability and stable mechanical properties of foamed concrete in EMAS has become a new research topic. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a method for preparing graphite tailings foamed concrete.
[0006] Another object of the present invention is to provide graphite tailings foamed concrete obtained by the above preparation method.
[0007] Another object of the present invention is to provide the application of the above-mentioned graphite tailings foamed concrete in the aircraft runway arresting system (EMAS).
[0008] The objective of this invention is achieved through the following technical solutions.
[0009] A method for preparing graphite tailings foamed concrete includes the following steps: Step 1: Mix cement, fine aggregate and fiber until uniformly mixed to obtain dry material. The ratio of cement, fine aggregate and fiber by mass parts is (110~150):(80~120):(0.4~0.9). The cement is rapid hardening sulfoaluminate cement, the fine aggregate is graphite tailings and the fiber is polypropylene fiber. In step 1, the stirring rate is 100-200 r / min, and the stirring time is 3-5 minutes.
[0010] Step 2: Mix the water-reducing agent, catalyst, and water evenly, add them to the dry materials, stir to obtain a mixed slurry, add the foaming agent and foam stabilizer to the mixed slurry, stir, add the accelerator and continue stirring to obtain foamed concrete slurry. The ratio of cement, water, water-reducing agent, catalyst, foaming agent, foam stabilizer and accelerator by mass is (110~150):(80~100):(1~2):(0.1~0.3):(5~6):(1.5~2.5):8.58. The water-reducing agent is a polycarboxylate-based water-reducing agent, the catalyst is MnO2, the foaming agent is hydrogen peroxide solution, the foam stabilizer is hydroxypropyl methylcellulose ether, and the accelerator is J85 type accelerator. In step 2, the stirring rate is 150~400 r / min, and the stirring time is 1~10 minutes.
[0011] In step 2, the hydrogen peroxide solution is a mixture of hydrogen peroxide and water, and the concentration of hydrogen peroxide in the hydrogen peroxide solution is 20~40wt%.
[0012] Step 3: Place the foamed concrete slurry in the mold, let it stand for at least 48 hours, remove the mold, and allow it to cure naturally for at least 28 days to obtain graphite tailings foamed concrete.
[0013] The graphite tailings foamed concrete obtained by the above preparation method.
[0014] The above-mentioned graphite tailings foamed concrete is used in the aircraft runway arresting system (EMAS).
[0015] In the above technical solution, the stress-collapse curve plateau segment of the graphite tailings foamed concrete... Less than 10%, of which, This represents the maximum stress value in the platform segment. This represents the average stress value of the platform segment.
[0016] In the above technical solution, the stress-collapse curve plateau segment of the graphite tailings foamed concrete... Greater than -10%, of which, This represents the minimum stress value of the platform segment.
[0017] In the above technical solution, the collapse strength variation rate of the graphite tailings foamed concrete is 15.8~17.6%.
[0018] In the above technical solution, the water absorption rate of the graphite tailings foam concrete is 23%.
[0019] In the above technical solution, the mass loss rate of the graphite tailings foamed concrete after 25 freeze-thaw cycles is less than 3.5%, and the freeze-thaw resistance coefficient is 0.92~1.04.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The graphite tailings foam concrete prepared by the present invention has water resistance, stable mechanical properties and good and stable energy absorption capacity, which meets the requirements of MH / T 5111-2015 "Specialty Materials Barrier Systems".
[0021] (2) The graphite tailings foam concrete of the present invention promotes the green, efficient, high-quality, high-value and large-scale utilization of graphite tailings, helps regional ecological civilization construction and creates good ecological benefits.
[0022] (3) The graphite tailings foam concrete prepared by the present invention uses industrial solid waste graphite tailings as fine aggregate, which greatly reduces its cost and the treatment cost of tailings stacking, brings economic value to cities that develop based on traditional resources, effectively saves energy and resources, increases industrial added value, and can create good social and economic benefits.
[0023] (4) Graphite tailings undergo crushing and grinding during the beneficiation process, resulting in reduced weight and larger surface area. When stored, they are prone to flow and collapse, causing damage to vegetation and injuries. In particular, they are prone to collapse and landslides during the rainy season. Utilizing graphite tailings as a resource can greatly reduce the occurrence of such safety accidents. Attached Figure Description
[0024] Figure 1 Photograph of foamed concrete from graphite tailings; Figure 2 (a) shows the stress-crushability curve and energy absorption curve of the graphite tailings foamed concrete prepared in Examples 1-4, and (b) shows the stress-crushability curve and energy absorption efficiency-crushability curve of the graphite tailings foamed concrete prepared in Example 3. Figure 3 SEM image of the graphite tailings foamed concrete prepared in Example 1 after 25 freeze-thaw cycles. Figure 4 The morphology of the graphite tailings foamed concrete prepared in Examples 1-4 after impact is shown. Detailed Implementation
[0025] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0026] The rapid-hardening sulfoaluminate cement (42.5R grade) was purchased from Tangshan Arctic Bear Building Materials Co., Ltd.
[0027] The graphite tailings originated from the Xinghe County mining area in Ulanqab City. The graphite tailings had a moisture content of 2.52% and a density of 1800 kg / m³. 3 The chemical composition and content of graphite tailings are shown in Table 1. Table 1
[0028] The polypropylene fiber was purchased from Shuangsen Building Materials Co., Ltd. in Langfang City, Hebei Province. The single fiber length is 12mm, the diameter of the polypropylene fiber is 6.57μm, the tensile strength of the polypropylene fiber is 1.61MPa, the elastic modulus of the polypropylene fiber is 42.13GPa, and the elongation at break of the polypropylene fiber is 1.26%.
[0029] The polycarboxylate superplasticizer was purchased from Shaanxi Qinfen Building Materials Co., Ltd., and its density is 1100 kg / m³. 3 The water reduction rate was 37%.
[0030] Both manganese dioxide (MnO2) and hydrogen peroxide (H2O2) solutions were purchased from Tianjin Damao Chemical Reagent Factory. The hydrogen peroxide concentration in the hydrogen peroxide (H2O2) solution was 30 wt%.
[0031] Hydroxypropyl methylcellulose ether (HPMC) was purchased from Shanghai Chenqi Chemical Technology Co., Ltd. The viscosity of HPMC is 200,000 and the fineness is greater than 80 mesh.
[0032] J85 type coagulant was purchased from Huaibei Xinda New Building Materials Co., Ltd.
[0033] In the following embodiments, the mechanical properties of graphite tailings foamed concrete were tested using a WGW-100G microcomputer-controlled universal testing machine. The mechanical property test procedures are described in "Restriction System for Special Materials" (MH / T 5111-2015). The loading rate of the WGW-100G microcomputer-controlled universal testing machine was set to 500 mm / min, and the maximum test force was set to 100 kN.
[0034] Examples 1-4
[0035] A method for preparing graphite tailings foamed concrete includes the following steps: Step 1: Accurately weigh the cement, fine aggregate and fiber using an electronic scale and place them in a mixing bucket. Use a hand mixer to stir at 150 r / min for 4 minutes until uniformly mixed to obtain dry material. The cement is rapid-hardening sulfoaluminate cement, the fine aggregate is graphite tailings, and the fiber is polypropylene fiber. The ratio of cement, fine aggregate and fiber by mass is W. Step 2: Mix the water-reducing agent, catalyst, and water evenly, add them to the dry material, and stir at a constant speed of 150 r / min for 10 minutes to obtain a uniformly mixed slurry. Add the foaming agent and foam stabilizer to the slurry and stir at a constant speed of 300 r / min for 1 minute. Add the accelerator and continue stirring at a constant speed of 300 r / min for 1 minute to obtain a uniformly mixed foamed concrete slurry. The water-reducing agent is a polycarboxylate-based water-reducing agent, the catalyst is MnO2, the foaming agent is hydrogen peroxide solution, the foam stabilizer is hydroxypropyl methylcellulose ether, and the accelerator is J85 type accelerator. By mass, the ratio of cement, water, water-reducing agent, catalyst, foaming agent, foam stabilizer, and accelerator is 143:85.8:1.14:0.11:5.5:1.72:8.58. Step 3: Place the foamed concrete slurry into a 100mm×100mm×100mm mold, let it stand for 48 hours, then remove the mold and allow it to cure naturally for 28 days to obtain graphite tailings foamed concrete.
[0036] The W and number of the graphite tailings foamed concrete prepared in Examples 1-4 are shown in Table 2.
[0037] Table 2
[0038] Figure 1 This is a photo of graphite tailings foamed concrete. In this concrete, manganese dioxide acts as a catalyst to fully utilize the foaming properties of hydrogen peroxide. Hydroxypropyl methylcellulose ether (HPMC) acts as a foam stabilizer to prevent the bubbles generated by the foaming agent from collapsing prematurely, thus prolonging their durability. A thin film can be formed at the interface between the foamed concrete slurry and the bubbles. J85 type accelerator acts as a settling accelerator to harden the foamed concrete in a short time, accelerating the stability of the bubble structure and preventing inconsistent setting and hardening rates between the inside and outside of the foamed concrete slurry during setting and hardening, which could lead to deformation of the internal and external structures of the graphite tailings foamed concrete and the appearance of localized fine cracks.
[0039] The test method for freeze-thaw resistance is as follows: The concrete was dried at 75℃ and weighed, recorded as m1 (the density of the graphite tailings foamed concrete at this time is ρ1). The dried concrete was placed in a constant temperature and humidity chamber (temperature: 20±2℃, relative humidity: ≥90%) for 48 hours. After that, the concrete was taken out, the surface moisture was absorbed, and the concrete was sealed in a plastic bag for N freeze-thaw cycles. After each freeze-thaw cycle, the concrete was taken out and dried to constant weight, recorded as m2 (the density of the graphite tailings foamed concrete at this time is ρ2). N is shown in Table 3. The concrete is one of the graphite tailings foamed concretes prepared in Examples 1 to 4. Each freeze-thaw cycle included: placing the concrete sealed in a plastic bag at -20±2℃ for 6 hours, and then placing it at room temperature for 5 hours.
[0040] m1 represents the mass of the graphite tailings foamed concrete corresponding to N=0 in Table 3; m2 represents the mass of the graphite tailings foamed concrete corresponding to N freeze-thaw cycles in Table 3 after N cycles (N=5, 10, 15, 20 and 25).
[0041] ρ1 represents the density of the graphite tailings foamed concrete corresponding to N=0 in Table 3. ρ2 represents the density of the graphite tailings foamed concrete after N freeze-thaw cycles (N=5, 10, 15, 20, and 25) in Table 3.
[0042] Mechanical property tests were conducted on graphite tailings foamed concrete (N=0) and graphite tailings foamed concrete after N freeze-thaw cycles. Stress-collapse curves were obtained, and the collapse strength of the graphite tailings foamed concrete was calculated based on these curves. The results are shown in Table 3. When N=0, the stress-collapse curve of the graphite tailings foamed concrete is as follows: Figure 2 As shown in (a).
[0043] Table 3
[0044] As shown in Table 3, the collapse strength of the graphite tailings foamed concrete prepared in Examples 1-4 first increases and then decreases with the increase of the proportion of graphite tailings. Among them, the collapse strength of the graphite tailings foamed concrete prepared in Examples 1-3 also increases with the increase of the proportion of graphite tailings. At this time, the graphite tailings play a skeletal role in the graphite tailings foamed concrete, and its supporting role can be well reflected. When the proportion of graphite tailings in cement reaches 1.0 (graphite tailings foamed concrete prepared in Example 4), the collapse strength of the graphite tailings foamed concrete decreases. Therefore, the graphite tailings foamed concrete prepared in Example 3 has the strongest collapse strength.
[0045] Further, based on the mass loss rate formula and frost resistance coefficient formula of the "Specialty Materials Barrier System" (MH / T 5111-2015), the mass loss rate (unit: %) and frost resistance coefficient of graphite tailings foamed concrete after 25 freeze-thaw cycles were calculated, as shown in Table 4. As can be seen from Table 4, the mass loss rate of the graphite tailings foamed concrete prepared in Examples 1 to 4 after 25 freeze-thaw cycles is less than 4%.
[0046] Table 4
[0047] Figure 2 (a) shows the stress-collapse curves and energy absorption curves of the graphite tailings foamed concrete prepared in Examples 1-4. Figure 2 As shown in (a), in the mechanical performance test, the energy absorbed by the graphite tailings foamed concrete prepared in Examples 1-4 gradually increased with the increase of the externally applied penetration load and the penetration depth. Furthermore, the proportion of graphite tailings in the graphite tailings foamed concrete prepared in Examples 1-4 also had a significant impact on the energy absorption capacity of the graphite tailings foamed concrete. The energy absorption capacity showed a trend of first increasing and then decreasing with the increase of the proportion of graphite tailings, reaching its peak when the proportion of graphite tailings in the cement was 0.8 (graphite tailings foamed concrete prepared in Example 3), meaning that the energy absorption capacity of the graphite tailings foamed concrete prepared in Example 3 was the strongest.
[0048] Figure 2 (b) shows the stress-crushability curve and energy absorption efficiency-crushability curve of the graphite tailings foamed concrete prepared in Example 3, from... Figure 2 As can be seen from (b), the energy absorption efficiency of the graphite tailings foam concrete prepared in Example 3 is at its peak when the crushing degree reaches 70%, which meets the requirement of greater than 60% in the "Specialty Materials Barrier Systems" MH / T 5111-2015.
[0049] The stress-crushability curves obtained from the mechanical property tests can be divided into four stages: the elastic deformation stage, the stress decrease stage, the plateau stage, and the compaction stage. In the plateau stage, the pores and cell walls at the fracture surface of the graphite tailings foamed concrete gradually undergo significant crushing and compaction, leading to localized densification. This increases the load-bearing capacity of the graphite tailings foamed concrete to a certain extent, thereby inducing strain hardening. Therefore, throughout the plateau stage, the stress of the graphite tailings foamed concrete exhibits varying degrees of fluctuation, reflecting that the graphite tailings foamed concrete simultaneously possesses strain softening and strain hardening behaviors. This fluctuation can also be seen as the result of the alternating coupling of strain softening and strain hardening.
[0050] Based on the stress-crushability curve of foamed concrete from graphite tailings, the stress deviation is calculated by taking the stress on the plateau section of the stress-crushability curve, and the maximum value of the stress deviation on the plateau section is used. , The maximum and minimum stress values for the platform segment are (the maximum and minimum stress values for the platform segment). , To evaluate the stability of the mechanical property curves (i.e., stress-collapse curves) of graphite tailings foamed concrete at the minimum stress value of the platform section (where N is the minimum stress value), the collapse strength change rate of graphite tailings foamed concrete (N=0) and graphite tailings foamed concrete after N freeze-thaw cycles (N=5, 10, 15, 20, and 25) is calculated using the following formula: ; ; in, η For stress deviation, For the stress of the platform segment, P represents the average stress of the platform segment (i.e., the collapse strength); λ is the rate of change of collapse strength, and P... N Pcrush strength is the collapse strength after N freeze-thaw cycles, and P0 is the collapse strength after 0 freeze-thaw cycles.
[0051] Graphite tailings foamed concrete (N=0) and graphite tailings foamed concrete after N freeze-thaw cycles. η Maximum sum η The minimum value and the rate of change of collapse strength are shown in Table 5. As can be seen from Table 5, within the range of 0 to 25 freeze-thaw cycles, the stress deviation of the stress-collapse strength plateau segment of the graphite tailings foam concrete prepared in Examples 2 to 3 is stable within ±10% of the design range. The rate of change of collapse strength after 25 freeze-thaw cycles is less than 20%, which meets the requirements of "Specialty Materials Barrier Systems" (MH / T5111-2015).
[0052] Table 5
[0053] Figure 3 The internal microstructure of the graphite tailings foamed concrete prepared in Example 1 after 25 freeze-thaw cycles is shown. Figure 3It is known that the graphite tailings foamed concrete prepared in Example 1 exhibits a needle-like crystalline microstructure within its pores. This is because the finer graphite tailings in the prepared graphite tailings foamed concrete have a filling effect, which not only enhances the fluidity of the slurry but also reduces collision damage during the preparation process, thereby optimizing the pore structure of the graphite tailings foamed concrete. Furthermore, the presence of a small amount of Al2O3 and CaO in the graphite tailings leads to secondary hydration, and the resulting hydration gel products fill the pore structure after the cement slurry has hardened, resulting in interwoven needle-like crystals that improve the mechanical properties of the graphite tailings foamed concrete.
[0054] Water resistance test: After drying the concrete in an electric heating drying oven (temperature 25±5℃) for 48 hours, remove it and weigh it, recording the weight as m0. Then, immerse the concrete in a water tank for 24 hours, ensuring the water level is 30mm above the top of the concrete. After immersion, remove the concrete, wipe the surface dry with absorbent paper, and weigh it again, recording the weight as m. g The concrete is the graphite tailings foamed concrete (N=0) prepared in Example 3, with dimensions of 100 mm × 100 mm × 100 mm.
[0055] Water absorption rate calculation formula: Water absorption rate = .
[0056] The water absorption rate of the graphite tailings foamed concrete prepared in Example 3 was 23%.
[0057] Mechanical property tests were conducted on the graphite tailings foamed concrete prepared in Example 3 after the "water resistance test" and the graphite tailings foamed concrete prepared in Example 3 without water immersion. According to the formulas for half-collapse energy and half-collapse energy softening coefficient in "Retaining Systems of Characteristic Materials" MH / T 5111-2015, the half-collapse energy softening coefficient of the graphite tailings foamed concrete prepared in Example 3 was calculated. The half-collapse energy softening coefficient of the graphite tailings foamed concrete prepared in Example 3 after water immersion was 0.8, which still meets the design requirement of half-collapse energy softening coefficient of 0.8~1.2 in "Retaining Systems of Characteristic Materials" MH / T 5111-2015. Therefore, the graphite tailings foamed concrete prepared in Example 3 has water resistance.
[0058] The graphite tailings foamed concrete prepared in Examples 1-4 after 25 freeze-thaw cycles was subjected to SHPB impact tests using an ALT1000 Hopkinson bar impact testing system. Impact velocities were 2 m / s, 3 m / s, 4 m / s, and 5 m / s, respectively. The incident and transmission bars of the ALT1000 Hopkinson bar impact testing system were both hollow aluminum rods, 2.5 m long and 50 mm in diameter. The projectile in the ALT1000 Hopkinson bar impact testing system was 800 mm long and 50 mm in diameter. Test results... Figure 4 As shown, by Figure 4 It can be seen that as the impact velocity increases, the graphite tailings foamed concrete changes from a blocky state to a powdery state after impact, until it is completely crushed. Furthermore, when the impact velocity exceeds 4 m / s, the morphological differences of the graphite tailings foamed concrete after impact are not significant. The degree of crushing of the graphite tailings foamed concrete after impact also varies with the proportion of graphite tailings. When the proportion of graphite tailings is low, the graphite tailings foamed concrete prepared in Examples 1 and 2 exhibits a fine powdery state at an impact velocity of 5 m / s, while when the proportion of graphite tailings is high, the graphite tailings foamed concrete prepared in Example 4 exhibits smaller particles at an impact velocity of 5 m / s. The graphite tailings foamed concrete prepared in Example 3 (graphite tailings accounting for 0.8% of the cement) maintains good integrity under impact load, and the particle size after impact crushing is large, exhibiting the strongest impact resistance, consistent with its mechanical properties.
[0059] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. An application of graphite tailings foamed concrete in aircraft runway arresting systems, wherein the preparation method of graphite tailings foamed concrete includes the following steps: Step 1: Mix cement, fine aggregate and fiber until uniformly mixed to obtain dry material. The ratio of cement, fine aggregate and fiber by mass parts is 143:114.4:0.
72. The cement is rapid hardening sulfoaluminate cement, the fine aggregate is graphite tailings and the fiber is polypropylene fiber. Step 2: Mix the water-reducing agent, catalyst, and water evenly, add them to the dry materials, stir to obtain a mixed slurry, add the foaming agent and foam stabilizer to the mixed slurry, stir, add the accelerator and continue stirring to obtain foamed concrete slurry. The ratio of cement, water, water-reducing agent, catalyst, foaming agent, foam stabilizer and accelerator by mass is 143:85.8:1.14:0.11:5.5:1.72:8.
58. The water-reducing agent is a polycarboxylate-based water-reducing agent, the catalyst is MnO2, the foaming agent is hydrogen peroxide solution, the foam stabilizer is hydroxypropyl methylcellulose ether, and the accelerator is J85 type accelerator. Step 3: Place the foamed concrete slurry in the mold, let it stand for at least 48 hours, remove the mold, and allow it to cure naturally for at least 28 days to obtain graphite tailings foamed concrete. Its characteristic is that the stress-collapse curve plateau segment of the graphite tailings foamed concrete is... Less than 10%, of which, This represents the maximum stress value in the platform segment. The average stress value of the platform segment; the stress-collapse curve of the platform segment of the graphite tailings foamed concrete. Greater than -10%, of which, This represents the minimum stress value in the platform segment; The mass loss rate of the graphite tailings foamed concrete after 25 freeze-thaw cycles was 2.3%, and the freeze-thaw resistance coefficient was 1.
04.
2. The application according to claim 1, characterized in that, In step 1, the stirring rate is 100~200 r / min, and the stirring time is 3~5 minutes.
3. The application according to claim 1, characterized in that, In step 2, the stirring rate is 150~400 r / min, and the stirring time is 1~10 minutes.
4. The application according to claim 1, characterized in that, The hydrogen peroxide solution is a mixture of hydrogen peroxide and water, and the concentration of hydrogen peroxide in the hydrogen peroxide solution is 20~40wt%.
5. The application according to claim 4, characterized in that, The shrinkage strength variation rate of the graphite tailings foamed concrete is 15.8~17.6%, and the water absorption rate of the graphite tailings foamed concrete is 23%.